The Use of Science Learning Resources in Physics Subjects at Secondary Schools in Enggano as The Outermost Island of Indonesia - Johan, H; Karyadi, B; Farid, M; Sipriyadi, S; Johan, S; Fitri, E A; Opilah, B S (Journal of physics. Conference series, 2022)
Enggano is one of the outer islands of Indonesia in the province of Bengkulu. Enggano Island has one junior high school and one high school as educational facilities. This study aims to analyze science learning resources in physics subjects at secondary schools in Enggano, the outermost island of Indonesia. This study uses a qualitative descriptive method. The data collection instruments used were questionnaires for students, teacher interview guidelines, and document analysis of teaching materials. Based on the study results, it is known that the infrastructure for learning activities on the island of Enggano has little variety. The teaching materials used are only sourced from the main textbook. Students do not have textbooks to study independently outside the classroom. Learning resources based on the local potential of the island of Enggano are not yet available. The results of the analysis of teaching materials documents show that students are only facilitated by using the main textbook during learning activities in the classroom. Class-based learning activities are often constrained by natural conditions and road access from residential areas to schools. The interview results show that teachers still need support in providing varied teaching materials and need training activities to develop teaching materials for classroom-based and blended learning activities. Thus, it can be concluded that learning resources in high school on the island of Enggano still require development and require training to increase teacher competence in developing science and physics teaching materials.